1988
DOI: 10.1136/oem.45.11.727
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and allergic symptoms in wool textile workers.

Abstract: An epidemiological study of 2153 workers in 15 West Yorkshire wool textile mills was conducted to determine relations between respiratory symptoms and exposure to inspirable wool mill dust. A questionnaire designed to elicit all the common respiratory symptoms was developed and tested, and administered to all workers willing to participate (85%). It was translated and administered in Urdu for the 385 workers from Pakistan whose English was not fluent. Symptoms investigated included cough and phlegm, wheezing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The use of quantitative measures of exposure has become more common (Love et al 1988;Huy et al 1991;Smid et al 1992;Wegman et al 1992;Gardiner et al 1993;Cullinan et al 1994;Halpin et al 1994), partly because they allow a more elaborate exploration of exposure-response relationships. Often, the use of quantitative intensity measures of exposure leads to the observation of steeper exposure-response gradients and larger relative risk estimates (Blair and Stewart 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The use of quantitative measures of exposure has become more common (Love et al 1988;Huy et al 1991;Smid et al 1992;Wegman et al 1992;Gardiner et al 1993;Cullinan et al 1994;Halpin et al 1994), partly because they allow a more elaborate exploration of exposure-response relationships. Often, the use of quantitative intensity measures of exposure leads to the observation of steeper exposure-response gradients and larger relative risk estimates (Blair and Stewart 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Chest tightness has also been shown to occur in wool mills in Turkey [Ozesmi et al, 19871 and Scotland [Love et al, 19881, but, in contrast to the present and the Scottish survey, byssinosis was found in the Turkish mills. Like Love et al [1988], we found significant association between smoking and dyspnea, as well as between smoking and chronic bronchitis.…”
Section: Questionnairementioning
confidence: 67%
“…Respiratory symptoms have been shown to be more prevalent in cotton industry workers than in the general population [Beck et al, 19841 and than in silk workers [Christiani et al, 19861. High prevalences have also been demonstrated in the wool industry [Love et al, 1988;Ozesmi et al, 19871, but no reports have demonstrated any increased risk of respiratory diseases in the MMF industry preparing yarn from nylon, rayon, etc.…”
Section: Questionnairementioning
confidence: 91%
See 1 more Smart Citation
“…*Routing instructions, and instructions for excluding subjects disabled by musculoskeletal disease, have not been shown, but are advisable in the use of the questionnaire. From the answers to questions 1-6 and also 7-12 gradings of exercise tolerance at best and at worst respectively can be derived on scales of [1][2][3][4][5][6][7] (note that the logic of the yes/no answers changes through the sequence). The gradings attributed to combinations of answers to the first six questions are shown on the right.…”
Section: Introductionmentioning
confidence: 99%